Arabic Writers Of Francophone Ancestry: Focus On Shaykh Ibrahim ̕al-kawlakhī ̕as-sinighālī (1900-1975) - Mikail Adebisi Folorunsho (The Journal of Studies in Language, Culture and Society)
Shaykh Ibrahim ’al-Kawlakhī ̕as-Sinighālī was a well-known Arabic scholar and Tijāniyyah leader in Senegal. It is quite impossible to classify his activities into only the Tijāniyyah Sūfī brotherhood or Islamic proselytization for which he became famous, because he contributed significantly to intellectual Jihād which culminated into the production of his voluminous Arabic literary works. He became a prominent figure in sub-Saharan Africa through the Tijāniyyah activities. A good number of works have been written on these activities while acute dearth of attention to his literary productions remains observable. This paper looked beyond his activities as a Sūfī by exploring his contribution to Arabic scholarship in Senegal and beyond. The paper drew the attention of researchers to a seemingly obscure aspect of his life. It revealed that the Shaykh combined Sufism effectively with literary production. Information obtained from the study could be a veritable tool in the efforts to identify and assess the Arabic scholars of Francophone provenance who have contributed significantly to Arabic literary activities in West Africa